The development model of living houses with the Mix Use gender-based pattern (case study: Kampung Gajahmungkur Semarang) - Murtini, Titin Woro; Harani, Arnis Rochma; Murti, Nindita Kresna; Wardhani, Mustika Kusumaning (Journal of Architecture and Urbanism, 2019)
The existence of Kampung Jajan Pasar in Gajahmungkur Administrative Village, as the village (kampong) in Semarang City that produces traditional snacks for its commodity, has made its people utilize their living houses as a production room to produce food for home industry. Having limited area and facing the demand to extend the rooms for their home industry, these villagers, mostly females, eventually add another use for rooms of their living houses (mix use). These living houses have become the socio-economic places which describe gender equality (for females) in business related to the utilization of rooms using mix use pattern. This research tries to describe the potency of the villagers and their village that has been appointed as the thematic village with topic scope of adaptation resilience at living house towards the production room function. This result is used as the base for the development model of living houses with the gender-based mix use pattern at Kampung Jajan Pasar in Gajahmungkur, Semarang. The data collecting method were literature studies, observations, interviews, and primary and secondary data extraction. The development of the model used graphic design model and the layout design. The given output is a graphic design model of living houses development based on gender and the layout of environmental space as the center of traditional snacks in Semarang City.